Stereotyping And Objectifying Women: A Semiotics Analysis In The Lyrics Of Melanie Martinez's 'Strawberry Shortcake' - Gracia Petra Theresa; M. Afifuloh; M. Aries Taufiq (Universitas Negeri Semarang, 2025)
Stereotyping and objectifying women has been threatening women’s existence and worth for ages. As a result, women have been trying to call out an action to confront and challenge these destructive threats through so many ways. Melanie Martinez is a female singer that often using her platform to raise awareness on woman’s struggles in society such as stereotyping and objectifying women itself. This research aims to uncover hidden meanings, stereotypes, and objectifications of women in song lyrics “Strawberry Shortcake” by Melanie Martinez. The purpose of this research is to raise understanding and awareness of women's harmful stereotypes of the “ideal” body image and body objectifications through the song lyrics. This research used descriptive qualitative method to collect and analyze data to reveal the stereotypes and objectifications based on the meaning of the song lyrics. The theoretical framework that were used to analyze the song lyrics was semiotics theory of denotation, connotation, and myth by Roland Bartes. The result shows that the song lyrics are more than just depicts the struggles of women to confront unrealistic stereotypes of beauty standards and the objectification towards their body, but it’s also a call out action for society to begin confronting and challenging it.